Developing and implementing a complex Complementary and Alternative (CAM) nursing intervention for breast and gynecologic cancer patients undergoing chemotherapy: report from the CONGO (complementary nursing in gynecologic oncology) study - Klafke, Nadja; Mahler, Cornelia; Hagens, Cornelia von; Bentner, Martina (Supportive care in cancer, 2016)
Purpose/objectivesThe purpose of this study was to develop a complex nursing intervention including complementary and alternative medicine (CAM) for breast and gynecologic cancer patients during chemotherapy to improve quality of life.Methods Data sources Theoretical framework and concepts, practical nursing knowledge, and evidence-based studies were compiled in interprofessional meetings. Data synthesis The final complex intervention consists of three autonomous, but interacting components: (1) CAM nursing package, (2) resource-oriented counseling, and (3) evidence-based information material on CAM. CAM interventions include acupressure, aromatherapy, compress, and massage, targeting 14 clinically relevant symptoms during chemotherapy. Participants receive these interventions during chemotherapy with instructions for self care. During a counseling interview, the patient’s needs and preferences are assessed by trained nurses. Furthermore, participants are equipped with evidence-based information material (booklet and DVD). Prior to study start, nurses attended training modules for administering CAM therapies and for communicating and counseling within the salutogenic approach.ConclusionsIt was possible to design a multimodal CAM nursing intervention based on a theoretical concept, evidence-based studies, and practical nursing experience targeting the prevention or relief of side-effects women suffer during chemotherapy. The systematic analysis of the CONGO study will contribute to evidence-based CAM nursing care within supportive cancer care.Implications for integrative cancer careOncology nurses play an important role in supportive CAM care of breast and gynecologic cancer patients in daily clinical practice. Within oncology outpatient services, the implementation of evidence-based CAM nursing interventions and counseling may contribute to understand the impact of nursing on patient quality of life and symptom relief. This can lead to a new understanding of the nurse’s professional role.
Published online: 2 December 2015
Gesehen am 31.10.2019